2012
DOI: 10.1016/j.jchromb.2012.01.024
|View full text |Cite
|
Sign up to set email alerts
|

Plasma persistence of 2-aminothiazoline-4-carboxylic acid in rat system determined by liquid chromatography tandem mass spectrometry

Abstract: 2-Aminothiazoline-4-carboxylic acid (ATCA) was intravenously injected to rats in order to investigate its plasma distribution. ATCA was extracted from plasma samples by solid phase extraction (SPE) and molecularly imprinted polymer stir bar sorption extraction (MIP-SBSE). Detection and quantification of ATCA were achieved by using liquid chromatography-tandem mass spectrometry (LC-MS/MS). It was found that the intravenously injected ATCA concentration quickly decreased to half within 2.5h in the rat system. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Although this study did not address the in vivo generation of ATCA from cyanide exposure, it is one of the first studies to address the distribution and elimination of ATCA. The plasma ATCA ranged from 0.96 to 18.5 M, and showed a consistent 5-fold increase over endogenous concentrations between 2.5 and 48 h post-exposure (Petrikovics et al, 2012). These findings suggest that the use of ATCA as a biomarker is promising, but further evaluation of the toxicokinetics of ATCA following cyanide exposure should be undertaken.…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…Although this study did not address the in vivo generation of ATCA from cyanide exposure, it is one of the first studies to address the distribution and elimination of ATCA. The plasma ATCA ranged from 0.96 to 18.5 M, and showed a consistent 5-fold increase over endogenous concentrations between 2.5 and 48 h post-exposure (Petrikovics et al, 2012). These findings suggest that the use of ATCA as a biomarker is promising, but further evaluation of the toxicokinetics of ATCA following cyanide exposure should be undertaken.…”
Section: Introductionmentioning
confidence: 78%
“…Evaluation of the toxicokinetic behavior of cyanide and its breakdown products provides insight into the best marker for verification of cyanide exposure. Such studies have been conducted for cyanide (Dirikolu et al, 2003;Leuschner et al, 1991;Sousa et al, 2003) and its major detoxification products, thiocyanate (Leuschner et al, 1991;Sousa et al, 2003) and ATCA (Petrikovics et al, 2012), in various animal models. The results of these studies are presented in Table 1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that BCAT1 plays a significant role in the development of chronic myeloid leukemia [67]. In addition, disorders of α-keto acid levels in biological fluids are related to diseases such as diabetes mellitus, maple syrup urine disease, and ketoacidosis [68,69]. Therefore, the analysis of α-keto acids is attracting increasing interest.…”
Section: α-Keto Acids and Their Metabolitesmentioning
confidence: 99%
“…SPE offered adequate precision of 5.9% RSD, but interferences derived from whole blood were detected near the ATCA peak. On the other hand, MIP-SBSE produced a single peak derived from ATCA, but the capacity was insufficient and the method suffered from low recoveries [69]. Lulinski et al synthesized a novel imprinted material in a dispersive SPE, providing a rapid (35 min for extraction) and low-cost clean-up technique [70].…”
Section: Carboxylic Acids Containing a Thiazole Ringmentioning
confidence: 99%